INVESTIGATING THE MECHANICAL PROPERTIES OF PLA POLYMER TENSILE TEST SAMPLES PRODUCED VIA 3D PRINTING IN VARIOUS ORIENTATIONS: FLAT, VERTICAL, AND 45 DEGREES (INTERNATIONAL JOURNAL OF MECHANICAL ENGINEERING AND TECHNOLOGY (IJMET), 2024)
In this research, the impact of build orientation on the tensile strength of poly (lactic acid) or PLA polymers was examined. Utilizing PLA filaments of 1.70mm diameter, tensile test samples were designed with SolidWorks software in accordance with the ASTM D638 specifications for plastics. Then, the samples were 3D printed in orientations of 45 degrees, flat to the base, and upright using a FDL 3D printer. The finished specimens were subjected to stress tests using a Gunt universal testing machine, where it was found that the flat orientation samples experienced the greatest tensile stress due to more efficient load distribution across the layers. On the other hand, the vertically printed samples showed the least tensile stress, suggesting less effective load transmission. Optical microscopy was employed to observe the print layer orientations of the materials.